2000
DOI: 10.1143/jjap.39.5987
|View full text |Cite
|
Sign up to set email alerts
|

Single-Oriented Growth of (111) Cu Film on Thin ZrN/Zr Bilayered Film for ULSI Metallization

Abstract: We investigated the influence of ZrN/Zr bilayered film thickness on the (111) Cu orientation and the thermal stability of the Cu/ZrN/Zr/Si contact system by X-ray diffraction and Auger electron spectroscopy analyses. We confirmed that the single-oriented growth of (111) Cu can be realized by interposing the ZrN (400 Å)/Zr (200 Å) bilayered film between Cu and Si. It was revealed that the (111) Cu/(111) ZrN/(002) Zr/(001) Si contact system is satisfactorily stable up to 600°C without undesirable interfacial rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Only one FCC phase was observed with the sputtering conditions used, and the crystal lattice constant was found to be in a good agreement with a (Ti, Zr)N solid solution, showing a ratio of Zr / (Ti + Zr) = 0.30. J. Probst et al [15] also observed the peak shift of (111) lattice plane AOhm-cm) for ZrN as compared to TiN (DH F 298 = À 80.5 kcal/mol, q = 21.7 AOhm-cm) suggest better thermochemical stability of ZrN [16]. Consequently, the properties of (Ti, Zr)N x films are extremely sensitive to the filmsT microstructures and chemical composition.…”
Section: Introductionmentioning
confidence: 96%
“…Only one FCC phase was observed with the sputtering conditions used, and the crystal lattice constant was found to be in a good agreement with a (Ti, Zr)N solid solution, showing a ratio of Zr / (Ti + Zr) = 0.30. J. Probst et al [15] also observed the peak shift of (111) lattice plane AOhm-cm) for ZrN as compared to TiN (DH F 298 = À 80.5 kcal/mol, q = 21.7 AOhm-cm) suggest better thermochemical stability of ZrN [16]. Consequently, the properties of (Ti, Zr)N x films are extremely sensitive to the filmsT microstructures and chemical composition.…”
Section: Introductionmentioning
confidence: 96%
“…Zirconium nitride (ZrN), like all nitrides of the transition metals, is a promising alternative material in many domains because of its excellent properties such as superior mechanical properties, high melting temperature (2980 8C) [1], high thermal stability [2,3], good electrical conductivity [4], which was widely used as diffusion barrier [5,6], hard coating [7,8], corrosion-resistant layer [9,10], and abrasion-resistant [11,12]. Considering the difference in heats of formation, ZrN can be formed more easily than TiN and TaN (DH f 298 = À365.2 kJ mol À1 for ZrN, DH f 298 = À337.8 kJ mol À1 for TiN, and DH f 298 = À252.3 kJ mol À1 for TaN) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been applied to synthesize ZrN x films, such as chemical vapor deposition (CVD) [16], plasma nitridation [17], ion-beam-assisted evaporation [18,19], vacuum-arc deposition [20], and reactive magnetron sputtering [2,3,9,14,21,22]. Among these various techniques, reactive sputtering is the most common technique and is widely used in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to realize the Cu(111) single-oriented state as a Cu seed layer on the diffusion barrier/SiO 2 system, as pointed out by Hara. 6) In a previous paper, 7) we reported that the sequential single-oriented growth of (111)Cu/(111)ZrN/(002)Zr trilayered films on (001)Si can be realized by interposing the ZrN(400Å)/Zr(200Å) bilayered film between Cu and Si. Because it has been known that the contact resistivity of the Zr/n + -Si system with the ZrSi 2 silicide is lower than those of conventional contact systems such as Ti/n + -Si and Ta/n + -Si which have been generally used, 8) we expect that Zr films will play a role as a good adhesion layer to Si.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the thermal stability of the Cu-Zr/ZrN/Zr/Si contact system was evaluated for comparison with that of the Cu/ZrN/Zr/Si system reported in a previous paper. 7) …”
Section: Introductionmentioning
confidence: 99%